Perceived stress during social isolation due to COVID-19 and cognitive impact on young university students (2022)
The long-lasting and uncontrollable nature of confinement as a measure to slow down the spread of COVID-19 represents a source of extrinsic and chronic stress that could affect cognitive processes, especially memory. The objective of this study is to analyze the influence of perceived stress during compulsory social isolation due to COVID-19 on daily memory and to explore the emotional impact of confinement. Participants were 128 young Colombian university students, who answered the Spanish version of the Perceived Stress Scale (EEP-10) and the Questionnaire on memory failures of daily life, according to their experience in the last month of confinement. The influence of global perceived stress, general distress and coping ability on memory lapses in daily life was analyzed using a factorial variance analysis. Participants reported emotions and thoughts associated with states of anxiety, depression, and stress during confinement. A significant effect of perceived stress on daily life memory failures was found, and a significant interaction between general distress and coping ability on everyday memory. These findings are in addition to those reported in previous studies on the negative impact of social isolation due to the CO-VID-19 pandemic on mental health. The association found between perceived stress and subjective memory complaints in university students may have repercussions in the educational field that must be studied in depth, considering the influence of coping capacity on cognitive performance in stressful situations.